Exploring the Competitive Advantage of B2B E-Commerce Business: Bitubi Company - Yogi Hartono; Jacob Donald Tan (Proceeding of International Conference on Global Innovation and Trend in Economics, 2022)
Reflecting on the success of B2C or C2C e-commerce not only in Indonesia but also worldwide, it is a unique case that B2B e-commerce struggle to achieve the same success. However, in recent years many B2B e-commerce start-ups have emerged, showcasing their respective unique selling point to tackle the various challenges present by the industry and trying to acquire as much market share as possible before the predicted boom of B2B e-commerce industry. In this research, the researcher uses Bitubi as the study case to analyze what and how its competitive advantage work against the challenges present by the industry to the extent of its position among other competitors in the industry. This research uses qualitative method with in-depth interview as the main data collection method with subjects ranging from various level of employees and MSMEs as the e-commerce user. Experienced sales team, voucher system, logistics service, and integrated technological system are some of the most impactful competitive advantages of Bitubi compared to its competitor in B2B e-commerce business. This study allows for other potential research directions such as in the context of legal and government policy.